UPAYA PENINGKATAN KEMAMPUAN BACA TULIS HITUNG (CALISTUNG ) DENGAN PENDEKATAN BEYOND CENTER AND CIRCLE TIME (BCCT) PADA SISWA KELAS B RAUDLOTUL ATHFAL (RA) TIMPIK SUSUKAN - ROBI'AH, NUR (2011)
Learning activities in Raudlotul Athfal (RA) Timpik who have passed tend to place the teacher as a center of learning (teacher center) and lectures become the primary choice learning strategies, in this case the teachers tend to dominate activity during learning while students tend to be passive. These conditions lead to learning outcomes can not yet meet expectations. This study aims to determine read write and calculate upgrades BCCT approach in B grade students RA Timpik of the school year 2010/2011. This research was conducted for 5 (five) months in B grade students RA Timpik. The methods of data collection in this study using tests and observation. Data collection tools include the item on test, guidelines for observation and test results sheet. The data analysis technique in this study include: (1) quantitative data with a comparative descriptive analysis, and (2) qualitative data with qualitative descriptive analysis. The results presented as follows: 1. BCCT approach can improve read write and calculate skills in B grade students RA Timpik Susukan, this is the mark with the increasing percentage of mastery learning as follows: (a) Learning the first cycle, the percentage of students who pass on aspects of reading as much as 25.87%; on aspects of writing as much as 12:23%; and on aspects of numeracy of 21:13%, (b) Learning Cycle II, the percentage of students who completed the aspect of reading as much as 53.3%; on aspects of writing as much as 34.4%, and on aspects of numeracy as much as 52.2%, and (c) Learning cycle III, the percentage Students who pass on aspects of reading as much as 86.7%; on aspects of writing as much as 72.3%, and on aspects of numeracy as much as 78.9%. 2. BCCT approach can increase students' activeness of read write and calculate in B grade students RA Timpik Susukan. It is characterized by the increased value of student activity, namely: the first cycle of learning activities 5.71 (enough). Cycle II is 7.43 (good) and cycle III is 8.86 (very good). This research can be used as a consideration for teachers who want to apply BCCT approach in learning, especially in the level of Early Childhood Education (ECD), as in RA because BCCT approach can make learning a fun and can attract students to improve of read write and calculate skills.